THE EFFECT OF PHYPHOX APPLICATION ASSISTANT GUIDED INQUIRIES ON ABILITY STUDENT CREATIVE THINKING - Wahyudi, Ismu; Ashra, Vina Aprilia; Suyanto, Eko (Jurnal Pendidikan Matematika dan IPA, 2022)
This study aims to determine the effect of using a guided inquiry-based phyphox smartphone sensor application on creative thinking skills and improvement. The sample of this research is the students of class X IPA 3 SMA N 1 Kotabumi. The research design used was One Group Pretest-Posttest. The treatment is in the form of partially elastic collision learning assisted by a guided inquiry-based phyphox application that can be processed using Microsoft Excel. Data on students' creative thinking skills were obtained using a description test instrument. The technique of analyzing student learning outcomes data is using Paired Sample T-Test. Based on the results of the study, the average score of creative thinking skills increased by 35%, the average N-gain was 0.52 sig. (2-tailed) the value was less than 0.05. The results of partially elastic collision learning using a phyphox smartphone sensor based on guided inquiry have a significant effect on increasing students' creative thinking skills.